2017
DOI: 10.1186/s13033-017-0146-2
|View full text |Cite
|
Sign up to set email alerts
|

Mental distress and associated factors among undergraduate students at the University of Hargeisa, Somaliland: a cross-sectional study

Abstract: BackgroundMental distress is a common finding among University students. Empirical research has confirmed that the University student population has a higher prevalence of mental disorder than the general population. However, no previous study has examined the mental health conditions of students in Somaliland.MethodsAn institution based cross-sectional study was conducted on a sample of 570 undergraduate students at the University of Hargeisa in October, 2013. Study subjects were selected using a stratified r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
45
7
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 27 publications
(34 reference statements)
9
45
7
10
Order By: Relevance
“…The current finding is lower than what was reported in previous studies in Ethiopian universities [38,68]. The first possible justification for the difference might be data collection instrument being used to screen mental distress [38,68]. The second possible reason for the difference could be data collection time in which exam was approaching [68].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The current finding is lower than what was reported in previous studies in Ethiopian universities [38,68]. The first possible justification for the difference might be data collection instrument being used to screen mental distress [38,68]. The second possible reason for the difference could be data collection time in which exam was approaching [68].…”
Section: Discussioncontrasting
confidence: 83%
“…The other explanation for the difference might be resulted from not using locally validated instrument [67]. The current finding is lower than what was reported in previous studies in Ethiopian universities [38,68]. The first possible justification for the difference might be data collection instrument being used to screen mental distress [38,68].…”
Section: Discussioncontrasting
confidence: 66%
“…About 13 articles were further excluded due to the differences in the study population and study settings. Among these, six were conducted in Saudi Arabia [21,22], Pakistan [23], Brazil [24], Egypt [25], and Somalia [26]. The other six studies were excluded because of their different study population (conducted other than college/university students) [27][28][29][30][31][32].…”
Section: Search Resultsmentioning
confidence: 99%
“…This situation can be observed in several countries around the world, and several risk factors for stress occurrence in women, according to regional characteristics, can be mentioned. 20 It is worth mentioning the conquest of space in the labor market by women, linked to the maintenance of an old family model, in which they remain responsible for household chores. This fact creates a female triple-journey situation, which is composed of work, study, and children.…”
Section: Objectivementioning
confidence: 99%
“…19 On the other hand, it can be observed that the greater occurrence of stress among women, when compared to men, may include the fact that they are more susceptible than men, and that they are more spontaneous in admitting stress or that they suffer more stress than regional men. 20 There are important considerations regarding the association between a) the variables age, marital status, sexual orientation, and number of children, and b) stress in university students. Even if there were not statistically significant values, stress occurred in all of these situations.…”
Section: Objectivementioning
confidence: 99%